Electron microscopic study of Saccharomyces cerevisiae rDNA chromatin replication. - Saffer, L D (Mol Cell Biol, 1986)
An electron microscopic study was made of the replication of rDNA chromatin of Saccharomyces cerevisiae. Two different methods were used to synchronize cells. cdc7-1 cells were raised to a restrictive temperature, whereas A364a cells were blocked with mating factor. Replication bubbles typically opened in the nontranscribed spacers of rDNA repeats in both cell types. The mean position of the center of these bubbles corresponds closely to a position where an autonomously replicating sequence previously has been mapped in an rDNA repeat. Clusters of replication bubbles containing up to four bubbles spaced one to three genes apart were seen opening in early S phase. IMAGES: